Percutaneous closure versus medical therapy for stroke with patent foramen Ovale: a systematic review and meta-analysis - Xin-Lin Zhang; Li-Na Kang; Lian Wang; Biao Xu (BMC Cardiovascular Disorders, 2018)
Abstract Background Patent foramen ovale (PFO) closure has emerged as a secondary prevention option in patients with PFO and cryptogenic stroke. However, the comparative efficacy and safety of percutaneous closure and medical therapy in patients with cryptogenic stroke and PFO remain unclear. Methods Randomized controlled trials (RCTs) and comparative observational studies that compared PFO closure against medical therapy, each with a minimal of 20 patients in the closure arm and 1-year follow-up were included. Results We analyzed 6961 patients from 20 studies (5 RCTs and 15 observational studies) with a median follow-up of 3.1 years. Moderate-quality evidence showed that PFO closure was associated with a significantly lower incidence of the composite outcome of ischemic stroke, transient ischemic attack (TIA), or all-cause death (odds ratio [OR]: 0.57; 95% confidence interval [CI]: 0.38 to 0.85; P = 0.006), mainly driven by lower incidence of stroke (OR: 0.39; 95% CI: 0.24 to 0.63; P < 0.001). The numbers needed to treat were 43 and 39 for the composite outcome and recurrent ischemic stroke respectively. PFO closure increased the risks for atrial fibrillation or atrial flutter (OR: 5.74; 95% CI: 3.08 to 10.70; P < 0.001; high-quality evidence) and pulmonary embolism (OR: 3.03; 95% CI: 1.06 to 8.63; P = 0.038; moderate-quality evidence), with the numbers needed to harm being 30 and 143 respectively. The risks for TIA, all-cause death, and major bleeding were not statistically different. Analyses limited to RCTs showed similar findings, as did a series of other subgroup analyses. Conclusion In conclusion, PFO closure reduced the incidences of stroke and the composite outcome of ischemic stroke, TIA, or all-cause death, but increased risks for atrial fibrillation or atrial flutter and pulmonary embolism compared with medical therapy.